PARAGON II – A single arm multicentre phase II study of neoadjuvant therapy using irinotecan bead in patients with resectable liver metastases from colorectal cancer. Issue 12 (December 2016) - Jones, R.P.; Malik, H.Z.; Fenwick, S.W.; Terlizzo, M.; O'Grady, E.; Stremitzer, S.; Gruenberger, T.; Rees, M.; Plant, G.; Figueras, J.; Albiol, M.; Adam, R.; et al.
Abstract: Purpose: Perioperative chemotherapy confers a 3-year progression free survival advantage following resection of colorectal liver metastases (CRLM), but is associated with significant toxicity. Chemoembolisation using drug eluting PVA microspheres loaded with irinotecan (DEBIRI) allows sustained delivery of drug directly to tumour, maximising response whilst minimising systemic exposure. This phase II single arm study examined the safety and feasibility of DEBIRI before resection of CRLM. Methods: Patients with resectable CRLM received lobar DEBIRI 1 month prior to surgery, with a radiological endpoint of near stasis. The trial had a primary end-point of tumour resectability (R0 resection). Secondary end-points included safety, pathologic tumour response and overall survival. Results: 40 patients received DEBIRI, with a median dose of 103 mg irinotecan (range 64–175 mg). Morbidity was low (2.5%, CTCAE grade 2) with no evidence of systemic chemotoxicity. All patients proceeded to surgery, with 38 undergoing resection (95%, R0 resection rate 74%). 30-day post-operative mortality was 5% (n = 2), with neither death TACE related. 66 lesions were resected, with histologic major or complete pathologic response seen in 77.3% of targeted lesions. At median follow up of 40.6 months, 12 patients (34.3%) had died of recurrent disease with a median overall survival of 50.9 months. Nominal 1, 3 and 5-year OS was 93, 78 & 49% respectively. Conclusions: Resection after neoadjuvant DEBIRI for CRLM is feasible and safe. Single treatment with DEBIRI resulted in tumour pathologic response and median overall survival comparable to that seen after systemic neoadjuvant chemotherapy. Registered at clinicaltrials.gov (NCT00844233 ).